Effects of Using Instructional Games on Vocabulary in Human Anatomy and Physiology in Sports Science Students at Rajabhat Maha Sarakham University, Thailand. - Potisaen, Jukdao; Potisaen, Trimit (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purpose of this quasi-experimental research was to investigate the effects of using instructional games on vocabulary in human anatomy and physiology in sports science students at Rajabhat Maha Sarakham University. The sample group of 32 first-year sports science students were selected with the purposive sampling random technique through enrolled in learning of Anatomy and Physiology-1 course in the academic year 2018. The research instruments were (1) the vocabulary game, (2) achievements test and (3) satisfied questionnaire Investigate on the vocabulary game. Statistically analyzed with descriptive statistic were means, standard deviation, and t-test. The research findings were summarized as follow: 1) the processing and the resulting efficiencies (E1/E2) through used instructional game on vocabulary in human anatomy and physiology-1 indicated that of standardized determination at 70.63/84.68, which was considered effective according to 70/70 criterion, 2) The mean average scores show that of vocabulary game performance at a higher level, students’ learning outcomes of their pre-test and post-test were differentiated significant at a level of 0.05 and 3) Students’ performances of their satisfactions with the vocabulary game indicate of the mean average score at higher ( = 4.51, S.D. = 0.45)